The effect of immediate dentin sealing on the bond strength of resin composite to dentin bonded with universal bonding agent: An in vitro study - Meda, Vineetha; Sampathi, Naga Lakshmi Reddy; Reddy, Upendra Natha; Neshaneni, Sathish Kumar; Satyavathi, Sri E (International Journal of Dental Materials, 2024)
Background: Dentin hypersensitivity is a common scenario encountered in dental practice. This issue can be treated by reducing dentin permeability and dentinal fluid flow. However, the desensitizing agents used may adversely affect the bonding of composite restorations to dentin.Aim: To evaluate the shear bond strength of restorative composites to dentin treated with silver diamine fluoride and self-etch bonding agent bonded using a universal bonding agent.Materials and methods: A total of 30 teeth were selected, and their occlusal surfaces were ground to expose a flat dentin surface. The teeth were then embedded in cold cure resin blocks. Depending on the treatment, the samples were randomly divided into three groups, with 10 in each. The samples in the group were untreated, in group 2 were treated with Silver Diamine Fluoride (SDF), and in group 3 with the sixth generation bonding agent (self-etch primer). After the treatment, the composite is bonded to the dentin surfaces and subjected to shear bond strength using the universal testing machine (UTM). The specimen was mounted on the custom-made jig and placed over the UTM. The load was applied at a cross-head speed of 1mm/min until debonding occurred at the dentin and composite interface, and the bond strength was computed in MPa. Overall comparisons were analyzed using the Kruskal-Wallis test. The Mann-Whitney U test was used for pair-wise comparisons, and the significance level was set at p < 0.05.Results: The lowest bond strength was observed with the dentin surfaces treated with silver diamine fluoride (Group 2), and the highest bond strength was for dentin treated with self-etch bonding agent (Group 3). Significant differences (p